Prognostic significance of multiparametric flow cytometry minimal residual disease at two time points after induction in pediatric acute myeloid leukemia - Zheng, Yongzhi; Pan, Lili; Li, Jian; Feng, Xiaoqin; Li, Chunfu; Zheng, Mincui; Mai, Huirong; Yang, Lihua; He, Yingyi; He, Xiangling; Xu, Honggui; Wen, Hong; et al. (BMC cancer, 2024)
Prompt response to induction chemotherapy is a prognostic factor in pediatric acute myeloid leukemia. In this study, we aimed to evaluate the prognostic significance of multiparametric flow cytometry-minimal residual disease (MFC-MRD), assessed at the end of the first and second induction courses. MFC-MRD was performed at the end of the first induction (TP1) in 524 patients and second induction (TP2) in 467 patients who were treated according to the modified Medical Research Council (UK) acute myeloid leukemia 15 protocol. Using a 0.1% cutoff level, patients with MFC-MRD at the two time points had lower event-free survival and overall survival. Only the TP2 MFC-MRD level could predict the outcome in a separate analysis of high and intermediate risks based on European LeukemiaNet risk stratification and KMT2A rearrangement. The TP2 MFC-MRD level could further differentiate the prognosis of patients into complete remission or non-complete remission based on morphological evaluation. Multivariate analysis indicated the TP2 MFC-MRD level as an independent adverse prognostic factor for event-free survival and overall survival. When comparing patients with MFC-MRD ≥ 0.1%, those who underwent hematopoietic stem cell transplant during the first complete remission had significantly higher 5-year event-free survival and overall survival and lower cumulative incidence of relapse than those who only received consolidation chemotherapy. The TP2 MFC-MRD level can predict the outcomes in pediatric patients with acute myeloid leukemia and help stratify post-remission treatment.